Pemberdayaan Kelompok UKM Berbasis Teknologi dan Pemasaran Digital di Nagori Dolok Maraja Kabupaten Simalungun - Irfandi, Irfandi; Zulkifli, Zulkifli; Hidayat, Taufik; Harahap, Mukti Hamjah; Panggabean, Deo Demonta; Syah, Dedy Husrizal (Journal of Industrial Community Empowerment, 2022)
This activity was carried out at the Zafira Snack Business Group Partners where partners are located in Nagori Dolok Maraja, Tapian Dolok District, Simalungun Regency. Nagori Dolok Maraja is one of the Nagori in Simalungun that is intense in assisting SMEs, this is shown by the Nagori program with PKK which always provides guidance and assistance to SMEs. Because as a buffer area for Lake Toba tourism and the Sei Mangkei Special Economic Zone as a great opportunity for marketing culinary businesses that can be used as souvenirs. The main problem in the economic activity of community groups is that they fail to get adequate profits due to inadequate management, marketing and technology systems plus the Covid-19 pandemic which makes people's purchasing power decline, thus affecting the income of these community groups. The broader Special Goal is to make partners become entrepreneurs who are ready to be independent based on technology and digital marketing and can prosper the people in Nagori Dolok Maraja. The program output targets include: 1). TTG Automatic machine for kneading culinary ingredients 2). TTG Zafira Snack culinary oil draining machine 3). Packaging, Brand and design of culinary product packaging 4). E-commerce websites, accounts on online stores and social networks. This activity is planned to be carried out using an educational method approach, counseling, production training, business management training, design and assistance to partners in an effort to improve quality and quantity so that partners can be ready and independent.